Constructing Soliton and Kink Solutions of PDE Models in Transport and Biology - Vladimirov, V.A.; Kutafina, E.V.; Pudelko, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We present a review of our recent works directed towards discovery of a periodic, kink-like and soliton-like travelling wave solutions within the models of transport phenomena and the mathematical biology. Analytical description of these wave patterns is carried out by means of our modification of the direct algebraic balance method. In the case when the analytical description fails, we propose to approximate invariant travelling wave solutions by means of an infinite series of exponential functions. The effectiveness of the method of approximation is demonstrated on a hyperbolic modification of Burgers equation.